Financial Sector Development and Poverty Alleviation in the SADC Region (Journal of Reviews on Global Economics, 2019)
Financial development is widely regarded as another conduit through which poverty can be reduced. The study empirically examines the relationship between financial sector development and poverty reduction in SADC countries utilising the Generalised Method of Moments technique for the period 1980 to 2017. The empirical results indicate that the effect of the different measures of financial sector development on poverty in the SADC region is mixed. Six out of nine financial development variables have a negative effect on poverty in the SADC region. In terms of financial depth, the empirical results reveal mixed outcomes. Results on financial system stability confirm the notion that a stable financial system is beneficial to the poor. The results also reveal that financial inclusion or access to financial services significantly reduces poverty in the SADC region. The results thus suggest that financial sector development is beneficial to the poor when it is inclusive and stable. The results imply that policies aimed at ensuring a stable financial system, which is also inclusive, should be pursued if the poor are to benefit from the financial system.